1996
DOI: 10.1038/384567a0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the kinase Rsk-2 associated with Coffin-Lowry syndrome

Abstract: The Coffin-Lowry syndrome (CLS), an X-linked disorder, is characterized by severe psychomotor retardation, facial and digital dysmorphisms, and progressive skeletal deformations. Genetic linkage analysis mapped the CLS locus to an interval of 2-3 megabases at Xp22.2. The gene coding for Rsk-2, a member of the growth-factor-regulated protein kinases, maps within the candidate interval, and was tested as a candidate gene for CLS. Initial screening for mutations in the gene for Rsk-2 in 76 unrelated CLS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
283
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(286 citation statements)
references
References 21 publications
3
283
0
Order By: Relevance
“…However, precise substrates for each member of the family are less well understood. RPS6KA3 was shown to be inactivated by mutations in the X-linked disorder Coffin-Lowry syndrome yet the highly related RPS6KA1 and RPS6KA2 kinases were found to be expressed at normal levels in these patients (Trivier et al, 1996;Bruning et al, 2000). This has been further confirmed by the generation of RPS6KA3 À/À mice (Dufresne et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
“…However, precise substrates for each member of the family are less well understood. RPS6KA3 was shown to be inactivated by mutations in the X-linked disorder Coffin-Lowry syndrome yet the highly related RPS6KA1 and RPS6KA2 kinases were found to be expressed at normal levels in these patients (Trivier et al, 1996;Bruning et al, 2000). This has been further confirmed by the generation of RPS6KA3 À/À mice (Dufresne et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
“…It was puri®ed as the main NGF-induced CREB-kinase in PC12 cells (Xing et al, 1996). Mutations in the RSK2 gene and loss of RSK2 activity have also been associated with Co n-Lowry syndrome (CLS) which is characterized by severe psychomotor retardation, facial and digital dymorphisms, and progressive skeletal deformations (Trivier et al, 1996;Young, 1988). EGF-induced CREB phosphorylation was lost in ®broblasts from CLS patients while there was no change in cAMP, UV or serum induced CREB phosphorylation (De Cesare et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicated that Rsk-2 was required for EGF stimulated H3 SerlO phosphorylation in vivo (Trivier et al, 1996;Sassone-Corsi et al, 1999).…”
Section: Chapter 4 Results and Discussionmentioning
confidence: 99%
“…Genetic and biochemical studies in yeast, D. melanogaster, and human cells have identified a new class of multiple protein complexes that utilize ATP to remodel nucleosome and chromatin structure (Bjorklund et al, 1999;Trivier et al, 1996;Tyler and Kadonaga, 1999;Workman and Kingston, 1998). In D. melanogaster, four different ATP-dependent chromatin remodeling complexes have been identified.…”
Section: Atp Dependent Chromatin Remodeling Machinerymentioning
confidence: 99%
See 1 more Smart Citation